The diameter of the acyclic Birkhoff polytope - Costa, L.
In this work we give an interpretation of vertices and edges of the acyclic Birkhoff polytope, Tn = Ωn (T), where T is a tree with n vertices, in terms of graph theory. We generalize a recent result relatively to the diameter of the graph G (Tn). © 2007 Elsevier Inc. All rights reserved.